Intraindustry Trade, High-Wage Jobs and the Wage Gap - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 1999)
Drawing on the empirical fact that the high-wage primary sector is characterized by monopolistic competition, the paper shows, using a dual labor market model, that intraindustry trade results in an expansion of high-wage-premium jobs along with a decline in the wage gap.